Comparison of various channel equalization techniques in OFDM system using different digital modulations - Pratima Manhas; M.K. Soni (Institute of Advanced Engineering and Science, 2016)
The nature of future wireless applications requires high data rates and for this OFDM technique is used. OFDM stands for orthogonal frequency division multiplexing and is a type of multi-carrier transmission where all the subcarriers are orthogonal to each other. At high data rates, the channel distortion to the data is very important and it is somewhat impossible to recover the transmitted data with a simple receiver. So a complex receiver structure is needed which uses computationally expensive equalization and channel estimation algorithms to estimate the channel. These estimations can be used within the received data to recover the originally transmitted data. OFDM can simplify the equalization problem by changing the frequency-selective channel into a flat channel. The radio channels in mobile radio systems are usually multipath fading channels that results in intersymbol interference (ISI) in the received signal. To remove ISI from the signal, many kind of equalizers can be used. The need for equalizers arises from the fact that the channel has amplitude and phase dispersion which results in the interference of the transmitted signals with one another which is known as ISI .So, to solve this problem equalizers are designed. Equalizer is intend to work in such a way that Bit Error Rate (BER) should be low and Signal-to-Noise Ratio (SNR) should be high. An equalizer within a receiver compensates for the average range of expected channel amplitude and delay characteristics. This paper deals with the various equalization techniques (LMS, RLS and CMA) used for OFDM system .A comparative analysis of different equalization technique in terms of BER is done using MATLAB Simulink.